The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15132939
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Bone Health in Young Chilean Adults with Phenylketonuria and Different Degrees of Compliance with the Phenylalanine Restricted Diet

Eugenia Rojas-Agurto,
María Jesús Leal-Witt,
Carolina Arias
et al.

Abstract: There are concerns about muscle and bone health in patients with Phenylketonuria (PKU). Our aim was to compare muscle mass, function, and bone health among young adults with PKU who maintained or suspended dietary treatment. Methods: Three groups were considered—PKU-1: 10 patients who used a protein substitute (PS) without phenylalanine (Phe); PKU-2: 14 patients who used the PS without Phe until eighteen years old and then practiced mostly a vegan diet; and 24 matched healthy controls. A 24 h recall survey, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…The included studies were published from 1994 [38] to 2023 [39], and their characteristics are detailed in Table 1. Four studies were conducted in Greece [25,27,40,41], three in Turkey [31,42,43], three in Spain [32,44,45], two in Austria [26,46], two in Chile [39,47], two in Japan [29,30], two in the United Kingdom [48,49], two in the USA [38,50], and one each in Germany [51], France [52], Poland [28], and Switzerland [53]. All studies, except for one case-control study [26], were cross-sectional and compared individuals with PKU to healthy controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies were published from 1994 [38] to 2023 [39], and their characteristics are detailed in Table 1. Four studies were conducted in Greece [25,27,40,41], three in Turkey [31,42,43], three in Spain [32,44,45], two in Austria [26,46], two in Chile [39,47], two in Japan [29,30], two in the United Kingdom [48,49], two in the USA [38,50], and one each in Germany [51], France [52], Poland [28], and Switzerland [53]. All studies, except for one case-control study [26], were cross-sectional and compared individuals with PKU to healthy controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All studies, except for one case-control study [26], were cross-sectional and compared individuals with PKU to healthy controls. The PKU groups varied from 10 [39,52] to 107 [28], while control groups ranged from 6 [38] to 1676 [49]. Five studies assessed children [25,27,28,31,40], one studied adolescents [43], children and adolescents were included in nine studies [26,32,38,41,42,45,46,50,51,53], six studies examined adults [29,30,39,48,49,52], and the remaining two studies had a mixed population [44,47].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, if parental supervision ensures high levels of treatment adherence during childhood, adolescents often stop following dietary restrictions [ 1 , 6 , 7 ]. Moreover, despite the risk of late-onset neurological deficits, adults also frequently discontinue diet therapy, running a further risk of suffering from a more systemic disease [ 8 , 9 , 10 , 11 ]. Accordingly, a systematic review identified age as one of the major factors associated with poor treatment adherence, highlighting a gradual decline in metabolic control from adolescence onward [ 12 ].…”
Section: Introductionmentioning
confidence: 99%